Fixed Points for Multivalued Suzuki Type (θ,R)-Contraction Mapping with Applications - Mujahid Abbas; Hira Iqbal; Adrian Petrusel (Journal of Function Spaces)
In this paper, we will introduce the concept of Suzuki type multivalued (θ,R)-contraction and we will prove some fixed point results in the setting of a metric space equipped with a binary relation. Our results generalize and extend various comparable results in the existing literature. Examples are provided to support the results proved here. As an application of our results, we obtain a homotopy result, proving the existence of a solution for a second-order differential equation and for a first-order fractional differential equation.